2009
DOI: 10.1590/s1413-35552009005000040
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da laserterapia de baixa potência na reposta oxidativa epidérmica induzida pela cicatrização de feridas

Abstract: Background: Therapeutic use of low-level laser in physical therapy has increased significantly. Objective: To assess the effects of low-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 36 publications
2
10
0
8
Order By: Relevance
“…Studies suggest that LPL, as well as HF, facilitate tissue repair of cutaneous wounds 7,9,12,16,[19][20][21] . Similar results, especially in relation to the laser, were found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies suggest that LPL, as well as HF, facilitate tissue repair of cutaneous wounds 7,9,12,16,[19][20][21] . Similar results, especially in relation to the laser, were found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, several studies have shown the benefits of the extensive use of the LPL in situations such as the treatment of soft tissue injuries, joint diseases, open wounds, pressure ulcers, among others [11][12][13][14] . The AlGaInP laser (660 nm) is a therapeutic light of the electromagnetic spectrum in the red line, whose irradiation in injured tissues triggers a series of physiological effects necessary for the process of wound cicatrization and repair at tissue and organic levels by means of the photobiomodulation process, in addition to causing therapeutic effects, such as: local analgesia, edema reduction and anti-inflammatory action 11,15 .…”
Section: Led (Light Emitting Diode) and The High Frequency Generatormentioning
confidence: 99%
See 1 more Smart Citation
“…O laser AlGaInP apresenta comprimento de onda de 670nm com luz vermelha visível, apresentando maior eficácia em lesões como feridas, úlceras e queimaduras (BUSNARDO; BIONDO-SIMÕES, 2010), com emissão de onda de forma pulsada (AGNE, 2004;KITCHEN, 2010). O laser AsGa tem comprimento de onda de 904nm, apresentando luz invisível, mais utilizado em lesões como doença articular, muscular e tendinosa, com emissão de onda de forma contínua, como demonstram alguns estudos (SILVEIRA, 2009 (PINTO et al, 2008;GONÇALVES et al, 2010) na otimização do processo cicatricial de tecidos. No entanto, ainda existem lacunas no meio científico sobre a melhor dose, tempo e comprimento de onda.…”
Section: Introductionunclassified
“…A terapia com laser (light amplification by stimulated emission of radiation -amplificação da luz por emissão estimulada de radiação) utiliza luz altamente organizada para estimular alterações fisiológicas. É considerada uma terapia não invasiva, indolor, não térmica e assépti-ca, sem efeitos colaterais, com boa relação custo-benefí-cio, que, aliado à segurança do tratamento, justificam o crescente interesse dos pesquisadores quanto ao mecanismo de ação e seus efeitos terapêuticos 9 . Os lasers em baixa intensidade ou em fotobiomodulação são agentes terapêuticos sem potencial destrutivo, com eficiente ação anti-inflamatória e analgésica, fatores esses que ajudam no reparo dos tecidos biológicos traumatizados 10,11 .…”
Section: Introductionunclassified